Pemahaman Murka dan Kasih Allah dalam Memanfaatkan "Peluang Emas" Pengabaran Injil Pribadi di Masa Pandemi Covid-19 - Edwin Gandaputra (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2020)
The problem of the Covid-19 pandemic is experienced by the church in carrying our religious activities, especially personal evangelism. Restrictions on religious activities hinder personal evangelism. The Covid-19 kills thousands of people around people in the church. The fear of death is part of the understanding of God’s wrath in the Old and the New Testaments. God's wrath is shadowed by God's love. God's work of salvation becomes God's work of love. The results of descriptive interpretive research on understanding God's wrath and love are a golden opportunity to overcome personal gospel preaching during the Covid-19 period. The church plans and develops the potential of the church congregation in multiplying the "golden" opportunities of evangelism. Church leaders can use data that is integrated with the service systematics to support evangelism. All elements of the church can reach more souls. Evangelists communicate the understanding of God's wrath and God's love is communicated through online media networks be ‘golden’ opportunity in personal evangelism. AbstrakMasalah pandemi Covid-19 dialami oleh gereja dalam menjalankan kegiatan keagamaan khususnya pengabaran Injil pribadi. Pembatasan kegiatan keagamaan menghambatkan pengabaran Injil pribadi. Virus covid-19 membunuh ribuan orang terjadi di sekitar gereja. Ketakutan kematian menjadi bagian dari pemahaman murka Allah dalam Perjanjian Lama dan Perjanjian Baru. Murka Allah dibayangi kasih Allah. Karya keselamatan Allah menjadi karya kasih Allah. Hasil penelitian deskriptif interpretatif tentang pemahaman murka dan kasih Allah menjadi peluang emas untuk mengatasi pengabaran Injil pribadi di masa covid-19. Gereja merencanakan dan mengembangkan potensi jemaat  gereja dalam mengali peluang ‘emas’ pengabaran Injil. Pemimpin gereja dapat menggunakan data yang diintergrasi dengan sistematika pelayanan mendukung pengabaran Injil. Seluruh elemen gereja dapat menjangkau lebih banyak jiwa-jiwa. Pengabar Injil mengkomunikasikan pemahaman murka Allah dan kasih Allah dikomunikasikan melalui jejaring media online menjadi peluang ‘emas’ dalam pengabaran Injil pribadi.